Optimization of Academic Outcomes and Talent Development: A Quantitative Analysis of Student Time Management Strategies and Challenges - Ayu, Niken; Rismawati, Rismawati (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
This study aims to explore how study habits, talent development, and challenges faced by students affect their strategies in managing time, which in turn can affect the balance between studies and other aspects of their lives. Quantitative methods were used in this study through distributing questionnaires to students of Universitas Muhammadiyah Palopo. Data were collected and analyzed using SPSS 26 and using the t-test to assess the effect of the independent variable on the dependent variable. The statistical results showed that students' study habits had a significant influence on their strategies in managing time. Talent development was also shown to have a significant influence, suggesting that students who are active in developing their talents may have a different approach in managing their time. In addition, the challenges students face also have a significant influence on how they manage their time. These findings underscore the importance of a holistic approach in supporting students to manage their time effectively to achieve a balance between studies, talent development, and overcoming the challenges they face.